(untitled) (Journal of Nepal Geological Society, 2016)
Land use and land cover is an important component in understanding the interactions of the human activities with the environment. Land use planning are widely recognized as key non-structural risk mitigation measures. In the present study, decadal land use changes in the Triyuga watershed has been assessed for the period between 1980 and 2015. Satellite images of Landsat (ETM, TM and OLI) have been used to prepare land use maps for respective period. The relationship between disaster loss, land use and meteorological factor (rainfall) has been evaluated. Significant correlation between the parameters has been obtained.